Synthesis and Acid Catalytic Activity of 1,5,3,7-Diazadiphosphocine-1,5-dicarboxylic Acids - Gyun Lee, Yong; Tae Kim, Sung; Il Jung, Dai; Tai Hanh, Jung (Asian Journal of Chemistry, 2015)
In order to synthesize new bioactive sompounds and contrasting agents, reactions of amino acids (glycine, aspartic acid and glutamic acid) with para formaldehyde and hypophosphorous acid were executed. Products are 3,7-dihydroxy-3,7-dioxoperhydro-1,5,3,7-diazadiphos-phocine-1,5-diacetic acid (4a), 2-[5-(1,2-dicarboxyethyl)-3,7-dihydroxy-3,7-dioxoperhydro-diazadiphosphocine-1-yl]-succinic acid (4b) and 3,7-dihydroxy-3,7-dioxoperhydro-1,5,3,7-diazadiphosphocine-1,5-di-(2-glutaric acid) (4c). As shown in Table-1, the reactions of 4a-c in presence of acid catalysts (all 100 % GC yields) gave only 8-phenyl-8-azabicyclo[3.2.1]octan-3-one (5) (4a; pH (1M) = 0.17, 4b; pH (1M) = 0.15, 4c; pH (1M) = 0.16). In case of inorganic acid catalysts, 8-phenyl-8-azabicyclo[3.2.1]octan-3-one (5) and N-phenyl pyrrole (6) (HCl: 5 = 89.4 and 6 = 10.3 %, H2SO4; 5 = 94.4 and 6 = 5.5 %, CH3COOH: 5 = 13 and 6 = 7.8 %, citric acid: 5 = 80.6 and 6 = 18.7 %) were synthesized. Because of selective acid catalytic ability of 4a-c, we will try reactivity studies as acid catalysts of 4a-c about all acid catalytic reactions.